Is it ever enough? Food consumption, satiation and obesity - Corinna Manig (Max Planck Institute of Economics, 2010)
In order to explain the growth of obesity in industrialized and transition economies, a behavioral approach to food intake and overconsumption of calories is presented. It is argued that changes in food consumption patterns are one of the main drivers behind the imbalance of calories consumed and calories spent. The inclusion of new types of food in the regular diet of individuals led to changes in the motives for eating. While the intake of nutrients has always been and still is a prime motive of food consumption, it will be argued that with a growing variety of food items other motives increasingly take over as major drivers of the expanding food intake. These other motives also cause that the internal signals indicating to the body when to close a consumption act now occur with delay. The interrelation of biological and psychological factors and changes in the composition of diet therefore forms the basis for weight gain and, in the long run, obesity.
urn:nbn:de:gbv:27-20110628-144931-9
Keywords: I19; D11; D83; 330; consumer behaviour; obesity; food consumption; needs; satiation processes; Körpergewicht; Nahrungsmittelkonsum; Ernährungsverhalten; Konsumgesellschaft; Industriestaaten; Transformationsstaaten